2023
DOI: 10.52547/pcnm.13.1.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Risk Perception and its Related Factors and Outcomes in Vulnerable Groups: A Systematic Review

Abstract: Background:The COVID-19 disease has worse outcomes in individuals with underlying diseases and elderly individuals. Therefore, identifying COVID-19 risk perception and its related factors and outcomes in vulnerable groups is essential for the health system. Objectives: This study aimed to determine COVID-19 risk perception, its related factors, and outcomes in vulnerable groups (individuals with underlying diseases, smokers, opioid addicts, the elderly, and pregnant women). Methods: This systematic review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The results of a qualitative study by Alqahtani et al 30 in Saudi Arabia also showed that risk perception is the basis of the tendency to deny risks or react with exaggeration in terms of precautionary reactions related to COVID‐19. This is a vicious cycle because the higher risk perception of contracting COVID‐19 can lead to an increase in anxiety and fear of chronic patients and subsequently cause postponement of treatment sessions and increase in avoidance behaviors 16 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of a qualitative study by Alqahtani et al 30 in Saudi Arabia also showed that risk perception is the basis of the tendency to deny risks or react with exaggeration in terms of precautionary reactions related to COVID‐19. This is a vicious cycle because the higher risk perception of contracting COVID‐19 can lead to an increase in anxiety and fear of chronic patients and subsequently cause postponement of treatment sessions and increase in avoidance behaviors 16 …”
Section: Discussionmentioning
confidence: 99%
“…This is a vicious cycle because the higher risk perception of contracting COVID-19 can lead to an increase in anxiety and fear of chronic patients and subsequently cause postponement of treatment sessions and increase in avoidance behaviors. 16 T A B L E 3 Regression analysis of EPPM constructs for COVID-19. In the present study, defensive avoidance was dependent variables influenced by perceived severity and fear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations